Rhamphothrips genus-group (Thysanoptera, Thripidae) in Japan, with three new species - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2018)
In Japan, no members of Rhamphothrips genus-group have hitherto been known, but three species of this group are here newly described from Japan: Exothrips yaeyamanus sp. n., Rhamphothrips nemunoki sp. n. and R. ogasawarensis sp. n. Moreover, an uncertain species of Exothrips is recorded from Okinawa on Poaceae.